2015
DOI: 10.1186/s12889-015-2034-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported symptoms and healthcare seeking in the general population -exploring “The Symptom Iceberg”

Abstract: BackgroundResearch has illustrated that the decision-making process regarding healthcare seeking for symptoms is complex and associated with a variety of factors, including gender differences. Enhanced understanding of the frequency of symptoms and the healthcare seeking behaviour in the general population may increase our knowledge of this complex field.The primary objective of this study was to estimate the prevalence of self-reported symptoms and the proportion of individuals reporting GP contact, in a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
103
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 33 publications
(35 reference statements)
16
103
1
Order By: Relevance
“…Back pain ranked second in women and third in men. This is consistent with previous population-based studies reporting musculoskeletal symptoms as the most prevalent symptoms38 39 or among the most prevalent symptoms4 5 8 in older adults.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Back pain ranked second in women and third in men. This is consistent with previous population-based studies reporting musculoskeletal symptoms as the most prevalent symptoms38 39 or among the most prevalent symptoms4 5 8 in older adults.…”
Section: Discussionsupporting
confidence: 93%
“…Not only did a limited number of population-based studies investigated this issue, many of these focused on middle-aged adults4–8 or even exclusively on middle-aged women 910 Similarly, many studies on older people focused on a single symptom such as back pain,11 neuropsychiatric,12 anxiety13 or urinary14 symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…However, there may be other differences between respondents and nonrespondents. An overall responder analysis of the entire study cohort including both genders showed that respondents were more often cohabiting, had higher educational levels, had higher income, were attached to the workforce and of Danish origin . If this is the case for the women in particular, the results of this study will most likely underestimate the true differences found.…”
Section: Discussionmentioning
confidence: 75%
“…Most laboratory-confirmed H7N9 cases were severe infections [3,25] , which could partly be attributed to the absence of mild infection report to the medical facilities, inadequate coverage of pathogen testing on attended mild and moderate infections due to excessive workload, and the lack of an efficient diag- nostic method, such as point-of-care testing. The iceberg phenomenon of reported H7N9 cases [26][27] led to an underestimation of the burden of this disease.…”
Section: Discussionmentioning
confidence: 99%